Transumbilical single-site laparoscopic resection of splenic papillary angioendothelioma in a pediatric patient: a rare case report and review of literature - Meng Kong; Meng Kong; Qingfei Zhai; Shisong Zhang; Shisong Zhang; Hongzhen Liu; Hongzhen Liu; Yuexia Bai; Shuai Chen; Shuai Chen; Jinhua Jia; Jinhua Jia; et al. (Frontiers in Oncology)
BackgroundSplenic papillary angioendothelioma (PILA) is a rare borderline vascular tumor that is often asymptomatic and typically identified incidentally during imaging studies. Owing to its nonspecific clinical presentation and diagnostic complexity, optimal management strategies, particularly in pediatric patients, remain understudied. This report describes a case of pediatric splenic PILA managed with spleen-preserving minimally invasive surgery.Case descriptionA 5-year-old boy presented with an incidentally detected splenic mass during abdominal ultrasound six months prior to admission. The patient was asymptomatic and had no prior medical history. The patient was 115 cm tall and weighed 20.5 kg when admitted to the hospital. In the past half year, there has been no obvious growth and development delay, nor have there been any significant changes in diet or weight. Preoperative imaging, including contrast-enhanced ultrasound (US), computed tomography (CT), and magnetic resonance imaging (MRI), revealed a well-circumscribed lesion (6.0 cm × 5.5 cm × 5.0 cm) at the splenic upper pole, exhibiting heterogeneous enhancement patterns suggestive of a vascular tumor. Following multidisciplinary evaluation, a transumbilical single-port laparoscopic exploration was performed. Intraoperative frozen-section histopathology revealed benign characteristics, suggesting the need for a spleen-sparing partial splenectomy. Definitive postoperative histopathological and immunohistochemical analyses confirmed the diagnosis of PILA, which was characterized by CD31, CD34, and ERG positivity.ConclusionsPediatric splenic PILA is diagnostically challenging because of its rarity and overlapping radiological features with other vascular neoplasms. Complete surgical excision and longitudinal surveillance are critical to mitigate the risk of local recurrence or metastasis, given the tumor’s borderline malignant potential. Single-port laparoscopic partial splenectomy represents a feasible, minimally invasive approach for pediatric patients, balancing oncological safety with preservation of splenic function. This case underscores the importance of integrating intraoperative frozen-section analysis and advanced imaging to guide surgical decision-making, particularly in children.